ON THE ERRORS IN PRACTICE OF OBSERVATIONS AND THEIR REDUCTIONS - Rosenbush, A. E. (Одеські астрономічні публікації, 2017)
Specifical errors are not rare in the practice of astrophysical observations. Examples of such errors are given.